TAṬWĪR AL-WASI̅LAH AT-TA‘LI̅MIYYAH AL-ILIKTRU̅NIYYAH AL-MU‘TAMADAH ALA̅ ASA̅S WE̅BLOG LI DA‘MI NAMU̅ŻAJ AT-TA‘LI̅M AL-MAD‘U̅M BI AL-WE̅B (WEB ENHANCED COURSE) - Restu Budiansyah Rizki; Fathur Rohman; Abdul Ghofur (STIQ Amuntai, 2023)
The rapid development of technology and communication based on the internet in this modern era has affected various aspects of human life, including the education world. The presence of internet developments in the education world has provided an alternative to the use of weblog-based electronic learning media (e-learning), which can be utilized in web-enhanced course models. This study used a research and development model adopted from Sugiyono's theories in 5 steps, namely: (1) Potential and Problems), (2) Data Collection, (3) Design, (4) Design Validation, and (5) Production. Research and development are based on the minimal use of e-learning media in the learning and teaching process. The research data was taken from 37 students of Hasyim Asy'ari Jombang University. The results of the research are in the form of weblog-based e-learning media products to support web-based learning models, which can be accessed on the website page https://daurohbahasa.blogspot.com/. The results of design validation from material experts included: the content aspect obtained an average score of 86% (very good), the language aspect received an average score of 80% (good), and the presentation aspect obtained an average score of 88.88% (very good). Design validation from media technology experts includes software engineering aspects getting an average score of 82.22% (very good), communication aspects getting an average score of 82.50% (very good), and visual aspects getting an average score of 78.88% (good). The production of this media development is then applied to learning Arabic language education. Based on the assessment of experts, this weblog-based electronic media product can be used in a web-enhanced course model.